Editorial (Journal of Parents and Teachers, 2012)
This editorial presents a number of Padres y Maestros focused on developmental psychology, which constitutes a frame of reference to support teaching action in the various educational stages. It includes articles on language development, the role of error, the adult as a guide or the role of the game.
Keywords: Developmental psychology; Developmental psychologists; Piaget.